Control data on endocrine sensitive endpoints for untreated Sprague-Dawley rats from the Ramazzini Institute colony - Manservisi, Fabiana; Falcioni, Laura; Bua, Luciano; Menghetti, Ilaria; Mandrioli, Daniele; Galeati, Giovanna; Spinaci, Marcella; Tamanini, Carlo; Belpoggi, Fiorella (European Journal of Oncology and Environmental Health, 2018)
Background and aim: Findings from laboratory animals as well as human studies suggest that Endocrine Disrupting Chemicals (EDCs) cause a number of reproductive health outcomes. Rats have been used extensively for developmental and reproductive physiology and endocrinology research and a number of endocrine sensitive endpoints have been well established in a variety of regulatory guidelines on rodent bioassays. We monitored the background data on some endocrine sensitive endpoints for untreated Sprague-Dawley rats from the Cesare Maltoni Cancer Research of the Ramazzini Institute colony (SD-CMCRC/RI). Materials and methods: General reproductive indices from dams and data for the entire litter were recorded. All the littermates were retained until the achievement of puberty and balanopreputial separation (BPS) was monitored in all the males; estrous cycle length and pattern were also evaluated in one female/litter. We compared our data with those provided by the Health and Environmental Sciences Institute (HESI) of the International Life Sciences Institute (ILSI). Results: Overall, reproductive indices and pre-post weaning litter data of SD-CMCRC/RI rats were comparable with those reported by ILSI. Conclusions: Procedures for monitoring and physiological biological variations in our SD-CMCRC/RI rats fall within the range of values typically obtained for the selected endpoints. Further investigations are suggested in order to verify whether retaining all pups to sexual maturation can improve the sensitivity to discriminate between natural variation and treatment effects. A more comprehensive analysis of other relevant endocrine sensitive endpoints should be performed in order to provide a representation of the normal developmental landmarks and endocrine values at different ages.